In situ immunization of a TLR9 agonist virus-like particle enhances anti-PD1 therapy. Issue 2 (15th October 2020) - Cheng, Yinwen; Lemke-Miltner, Caitlin D; Wongpattaraworakul, Wattawan; Wang, Zhaoming; Chan, Carlos H F; Salem, Aliasger K; Weiner, George J; Simons, Andrean L
Abstract : Background: CMP-001 is a novel Toll-like receptor-9 agonist that consists of an unmethylated CpG-A motif-rich G10 oligodeoxynucleotide (ODN) encapsulated in virus-like particles. In situ vaccination of CMP-001 is believed to activate local tumor-associated plasmacytoid dendritic cells (pDCs) leading to type I interferon secretion and tumor antigen presentation to T cells and systemic antitumor T cell responses. This study is designed to investigate if CMP-001 would enhance head and neck squamous cell carcinoma (HNSCC) tumor response to anti-programmed cell death protein-1 (anti-PD-1) therapy in a human papilloma virus-positive (HPV+) tumor mouse model. Methods: Immune cell activation in response to CMP-001±anti-Qβ was performed using co-cultures of peripheral blood mononuclear cells and HPV+/HPV- HNSCC cells and then analyzed by flow cytometry. In situ vaccination with CMP-001 alone and in combination with anti-PD-1 was investigated in C57BL/6 mice-bearing mEERL HNSCC tumors and analyzed for anti-Qβ development, antitumor response, survival and immune cell recruitment. The role of antitumor immune response due to CMP-001+anti-PD-1 treatment was investigated by the depletion of natural killer (NK), CD4 + T, and CD8 + T cells. Results: Results showed that the activity of CMP-001 on immune cell (pDCs, monocytes, CD4+/CD8+ T cells and NK cells) activation depends on the presence of anti-Qβ. A 2-week 'priming' period after subcutaneous administration of CMP-001 was required for robust anti-Qβ development in mice. In situ vaccination of CMP-001 was superior to unencapsulated G10 CpG-A ODN at suppressing both injected and uninjected (distant) tumors. In situ vaccination of CMP-001 in combination with anti-PD-1 therapy induced durable tumor regression at injected and distant tumors and significantly prolonged mouse survival compared with anti-PD-1 therapy alone. The antitumor effect of CMP-001+anti-PD-1 was accompanied by increased interferon gamma (IFNγ) + CD4 + /CD8 + T cells compared with control-treated mice. The therapeutic and abscopal effect of CMP-001+ anti-PD-1 therapy was completely abrogated by CD8 + T cell depletion. Conclusions: These results demonstrate that in situ vaccination with CMP-001 can induce both local and abscopal antitumor immune responses. Additionally, the antitumor efficacy of CMP-001 combined with α-PD-1 therapy warrants further study as a novel immunotherapeutic strategy for the treatment of HNSCC.